Talk of the Master Rita Jimenez official Library of Congress of the United States - Jiménez, Rita (1995)
Talk given by the official of the Congress of the United States the Master Rita Jiménez in the inauguration of the courses of Bachillerato in Librarianship, Documentation and Information of the National University on March 14, 1995.